(untitled) (Revista Rupturas, 2025)
This study analyzes the public policies developed by Costa Rica to bridge the digital divide. It examines the actions implemented by the governing and regulatory body. The actions and results obtained are evaluated, concluding that the policies have been insufficient, ineffective, and characterized by a lack of institutional coordination in achieving the objectives. The absence of a baseline, the limited capacity to execute the funds from FONATEL, an opening conducted without sufficient conditions for providers, the minimal competition among suppliers, and the failure to apply international best practices regarding the requirements for providers to bridge the digital divide have all been negative factors in tackling this issue.